Factors Affecting Oral Health in Non-Commissioned Soldiers of Bangladesh Army attended the Dhaka Combined Military Hospital - Saha, Arup Kumar; Khan, Most Shahana Afroge; Al Mamun, Shaik Abdullah; Das, Diti Rani; Uddin, Helal; Kamal, Md Mustafa (City Dental College Journal, 2018)
Aims: A descriptive type of cross-sectional study was conducted comprising 100 non-commissioned soldiers of Bangladesh Army attended Dhaka combined military hospital (CMH) during January to July 2012, to find out the factors affecting their oral health. Materials and Methods: Data were collected by structured questionnaire. Collected data were compiled, tabulated, analyzed by computer using SPSS version 16.0. Results: Mean age of the respondents was 30.16±5.09 (range 20- 41) years where about 60% were married.Most (91%) of themcompleted secondary school certificate. Eightypercent (80%) lived in barracks and 97% had idea about dental diseases and 3% had not.Of all, 73% respondents brushed their teeth once daily and 27%, twice daily.Majority(76%)respondents brushed their teeth at morning and the lowest 11% after breakfast and the rest (13%) brushed their teeth at bed time.Ninety nine percent(99%) respondents used tooth paste as cleaning materials and only 1% respondents used something else.In this study, 40.0% visited dentist once in a year, 17% twice in a year and 43% did never visit dentist without dental problem. Usually48% visited dental chamber for gum bleeding and only 1%visited for regular dental checkups. Among the respondents, 36% visited dental chamber for pain and 15% visited dental chamber for detection of dental caries by themselves. The notable bad habits were not observed among 84.0% of the respondents. A few respondents had smoking (6.0%), betel nut chewing (4.0%) and snuff dipping (3.0%)habits. Of all,63% of the respondents had swelling of gum and 37% had no swelling of gum. Presence and absence of calculus on the gingival margin were found 47% and 53%, respectively. In view of individual perspective,2DMFT had among 40.0% respondents, followed by 1DMFT, 29%, 4DMFT,12%, 3DMFT, 3.0% and 16% respondents had no DMFT. Conclusions: Overall findings suggest that the factors that affect the oral health were smoking, frequency of tooth brushing, having some bat habits and visit to dentist when dental symptoms such as bleeding gums or toothache occurred. Clinical factors included bleeding and swollen gums, toothache and caries. DOI: http://dx.doi.org/10.3329/cdcj.v10i1.13737 City Dent. Coll. J Volume-10, Number-1, January-2013